On convergence of complex power series with independent random coefficients - Meredov, B.; Мередов, Б.; Мередов, Б. (Institute of Mathematics, NAS of Ukraine, 1995)
We find the domains of convergence and analyticity of Maclaurin and Laurent random power series.